2019
DOI: 10.1021/acs.chemmater.9b01908
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Vibrational Entropy as Driving Parameter of Flexibility in the Metal–Organic Framework ZIF-4(Zn)

Abstract: Please cite only the published version using the reference above. This is the citation assigned by the publisher at the time of issuing the AAM. Please check the publisher's website for any updates. This is the author's final, peer-reviewed manuscript as accepted for publication (AAM). The version presented here may differ from the published version, or version of record, available through the publisher's website. This version does not track changes, errata, or withdrawals on the publisher's site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 78 publications
2
39
0
1
Order By: Relevance
“…From comparing Δ A with Δ U , it can be observed that the bistability of Cu 2 (bdc) 2 dabco is mainly driven by Δ U , and that the np form is destabilised compared to the lp form due to its unfavourable − T Δ S . This behaviour is in agreement with the general rule that the crystallographically less dense structure has a higher vibrational entropy [12, 58, 59] . This tendency has also been observed for MIL‐53(Al) [11, 60] and MIL‐53(Cr) [10] and has been explained by only considering vibrational entropy contributions.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…From comparing Δ A with Δ U , it can be observed that the bistability of Cu 2 (bdc) 2 dabco is mainly driven by Δ U , and that the np form is destabilised compared to the lp form due to its unfavourable − T Δ S . This behaviour is in agreement with the general rule that the crystallographically less dense structure has a higher vibrational entropy [12, 58, 59] . This tendency has also been observed for MIL‐53(Al) [11, 60] and MIL‐53(Cr) [10] and has been explained by only considering vibrational entropy contributions.…”
Section: Resultssupporting
confidence: 89%
“…Comparing this situation to other flexible MOFs, we here show that Cu 2 (DB‐bdc) 2 dabco represents the first example in which the physicochemical properties of the flexible MOF are governed by configurational entropy. For instance, it is established that the phase transition in ZIF‐4(Zn) is based on a delicate balance between dispersion interactions and vibrational entropy, where the lp (high temperature) phase of ZIF‐4(Zn) comes with a gain in vibrational entropy driven by a softening of low frequency modes [12] . Likewise, the np to lp phase transition in the well‐studied MOF MIL‐53 has been shown to be driven by vibrational entropy only [9, 10, 60] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again taking the x Se =0.5 model as an example, the largest difference in E n between two structures is 3.8 meV atom −1 (0.36 kJ mol −1 atom −1 ), whereas the difference in the zero point energies is 0.06 kJ mol −1 atom −1 and the difference in A n vib at 900 K is 2.06 kJ mol −1 atom −1 . Given the number of examples in the literature showing that differences in vibrational free energy-in particular the vibrational entropy-are a key driver of temperature-induced phase transitions [42,[44][45][46], and are important in the determining the stability of alloy systems [43,47,48], this finding is not surprising, but is nonetheless noteworthy.…”
Section: Resultsmentioning
confidence: 99%
“…22 This suggests that temperature-induced phase transitions might be uncovered with careful comprehensive variable temperature structural and calorimetric studies, as in (NH 4 ) 2 {Ni [Cd(SCN) 6 ]}, which undergoes an order-disorder transition associated with the NH 4 + cation at around 120 K. 23 Optimisation of the orientational order of A-site cations towards ferroic order might be possible through crystal-engineering, by tuning the hydrogen-bonding or introducing halogen-bonding moieties, 44 and by deepening our understanding of the role of framework entropy in NCS-perovskites. 45…”
Section: Gua(scn) and Hydrogen Bondingmentioning
confidence: 99%